Implementation of Return to Learn Protocols for Student Athletes with Sport and Recreation Related Concussion: An Integrative Review of Perceptions, Challenges and Successes. (February 2023) - Fetta, Joseph; Starkweather, Angela; Huggins, Robert; Van Hoof, Thomas; Casa, Douglas; Gill, Jessica
Concussion or mild traumatic brain injury (mTBI) is a common phenomenon in the United States, with up to 3.6 million sport-related mTBIs diagnosed annually. Return to learn protocols have been developed to facilitate the reintegration of students into school after mTBI, however, the implementation of return to learn protocols varies significantly across geographic regions and school districts. An integrative review of the literature was performed using Whittemore and Knalf's methodology. A search of published literature was conducted using the PRISMA checklist. Database searches were conducted from March 2, 019 to October 2, 021 using the terms "mild traumatic brain injury" and "return to learn." Twenty-eight publications were included. Three themes were derived from this review: lack of policy, poor staff education on concussion symptoms and stakeholder communication breakdown. The development of communication patterns and use of a return to learn protocol could facilitate a gradual return to full academic workload after concussion.